Prognostic factors in phyllodes tumours of the breast: retrospective study on 166 consecutive cases. Issue 5 (5th October 2020) - Di Liso, Elisabetta; Bottosso, Michele; Lo Mele, Marcello; Tsvetkova, Vassilena; Dieci, Maria Vittoria; Miglietta, Federica; Falci, Cristina; Faggioni, Giovanni; Tasca, Giulia; Giorgi, Carlo Alberto; Giarratano, Tommaso; Mioranza, Eleonora; et al.
Abstract : Background: Phyllodes tumours (PTs) are rare fibroepithelial tumours accounting for <1% of all breast tumours. We assessed clinicopathological features and their prognostic effect in a single-institution patients' cohort. Methods: Patients diagnosed with PT between 2001 and 2018 at our institution were identified. Clinical, surgical and pathological features were collected. Phyllodes-related relapse was defined as locoregional or distant recurrence (contralateral excluded), whichever first. Results: A total of 166 patients were included: 115 with benign, 30 with borderline and 21 with malignant PTs. Features associated with malignant PT were younger age, larger T size, higher mitotic count, marked cytological atypia, stromal overgrowth, stromal hypercellularity, necrosis and heterologous differentiation (all p<0.01). The majority of patients with malignant PT underwent mastectomy (63.2% vs 3% of benign/borderline, p<0.001) and had negative surgical margins (83.3%). 4-year cumulative phyllodes-related relapse incidence was 7% for benign/borderline PT and 21.3% for malignant PT (p=0.107). In the entire cohort, marked cellular atypia and heterologous differentiation were associated with worse phyllodes-related relapse-free survival (HR 14.10, p=0.036 for marked vs mild atypia; HR 4.21, p=0.031 for heterologous differentiation present vs absent). For patients with benign PT, larger tumour size was associated with worse phyllodes-related relapse-free survival (HR 9.67, p=0.013 for T>5 cm vs T≤2 cm). Higher tumour-infiltrating lymphocytes (TILs) were associated with borderline and malignant PT (p=0.023); TILs were not associated with phyllodes-related relapse-free survival (HR 0.58, p=0.361 for TILs>2% vs≤2%). Overall, four patients died because of PT: three patients with malignant and one with borderline PT. Conclusions: Patients with malignant PT had increased rates of phyllodes-related relapse and phyllodes-related death. Cellular atypia and heterologous differentiation were poor prognostic factors in the entire cohort; large tumour size was associated with an increased risk of phyllodes-related relapse in benign PT.